Analysis of Gen Z's Perception of the Green Dot Label on Halal Cosmetic Products: A Case Study in Muara Telang District, South Sumatra - Utami, Renita Dian; Junaidi, Heri; Rusdi, Muhammad (Economic: Journal Economic and Business, 2025)
Cosmetics have been known for centuries and have undergone significant transformation, especially since the 19th century when packaging began to attract public attention. In the modern Islamic economic context, cosmetic products must not only meet halal requirements but also align with environmental values. This study aims to explore the understanding of Generation Z in Muara Telang Village, South Sumatra, regarding the Green Dot symbol found on halal-labeled cosmetic products, and to analyze how this understanding influences their consumption preferences. Using a qualitative field research method, data were collected through interviews and documentation from local shop owners and consumers. The findings reveal that most Generation Z respondents in Muara Telang have limited knowledge about the Green Dot symbol. Despite this, they prioritize halal certification and other product attributes such as price and brand when choosing cosmetics. The lack of awareness about environmental labeling highlights a gap between ecological literacy and Islamic economic principles. The study concludes that better education is needed to integrate sustainability with halal consumption.